Предмет: Алгебра,
автор: arinaminina20
Упростите выражение:
(2x-1)²+(2x+1)*(2x-1)=
Ответы
Автор ответа:
0
4х²-4х+1+4х²-2х+2х-1= -4х
вроде так.....
вроде так.....
Автор ответа:
0
2x²-2*2*1(=4)+1+4x²+2x+2x-1=6x²+4x-4
дальше как квадратное уравнение
дальше как квадратное уравнение
Похожие вопросы
Предмет: Українська мова,
автор: Аноним
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: nikzaytsev202131
Предмет: История,
автор: terminator40830
Предмет: Литература,
автор: trusova03062002